2000
DOI: 10.1103/physrevb.61.r13357
|View full text |Cite
|
Sign up to set email alerts
|

Random matrix model for quantum dots with interactions and the conductance peak spacing distribution

Abstract: We introduce a random interaction matrix model (RIMM) for finite-size strongly interacting fermionic systems whose single-particle dynamics is chaotic. The model is applied to Coulomb blockade quantum dots with irregular shape to describe the crossover of the peak spacing distribution from a Wigner-Dyson to a Gaussian-like distribution. The crossover is universal within the random matrix model and is shown to depend on a single parameter: a scaled fluctuation width of the interaction matrix elements. The cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 23 publications
2
39
0
Order By: Relevance
“…The matrices T parameterize the coset space UOSP(1, 1/1, 1)/[UOSP(1, 1)⊗UOSP(1, 1)], and σ (0) is a diagonal supermatrix of dimension four with entries given by Eq. (29) in the usual way [34]. Using this and the saddle-point solution in the expression of the effective Lagrangean, the first-order term in ǫ takes the canonical form…”
Section: Saddle Pointmentioning
confidence: 99%
“…The matrices T parameterize the coset space UOSP(1, 1/1, 1)/[UOSP(1, 1)⊗UOSP(1, 1)], and σ (0) is a diagonal supermatrix of dimension four with entries given by Eq. (29) in the usual way [34]. Using this and the saddle-point solution in the expression of the effective Lagrangean, the first-order term in ǫ takes the canonical form…”
Section: Saddle Pointmentioning
confidence: 99%
“…25,26 The spectral properties of these embedded ensembles were recently analyzed using an eigenvector expansion of the second moments. 27,28 Combined with a random-matrix one-body part, such a two-body ensemble was used to study interaction effects 29,30 and ground-state magnetization 31 in quantum dots with a small number of electrons. The spin structure of a system with a spin-conserving random interaction was studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2,3,4,5,6,7,8,9,10 Recent experiments 1,2,3 on the distribution of the inverse compressibility, which can be measured by conductance peak spacing, in the Coulomb-blockade regime have shown that the standard random matrix theory fails to explain the observed fluctuations; this implies that charging energy fluctuations may play a dominant role in the inverse-compressibility fluctuations. In particular, the distribution was observed to take a Gaussian-like symmetric form with non-Gaussian tails.…”
Section: Introductionmentioning
confidence: 99%